2016
DOI: 10.18100/ijamec.270656
|View full text |Cite
|
Sign up to set email alerts
|

Learning Based Experimental Approach For Condition Monitoring Using Laser Cameras In Railway Tracks

Abstract: Abstract:Detecting the rail surface faults is one of the most important components of railway inspection process which should be performed periodically. Today, the railway inspection process is commonly performed using computer vision. Performing railway inspection based on image processing can lead to false-positive results. The fact that the oil and dust residues occurring on railway surfaces can be detected as an error by the image processing software can lead to loss of time and additional costs in the rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
0
13
0
2
Order By: Relevance
“…Cao et al [ 29 ] proposed a defect inspection method of rail surface based on the line-structured light. Santur et al [ 30 ] described a computer-vision based approach allowing for a fast-contactless detection of the rail surface and lateral defects such as fracture, scouring and wear with high accuracy. However, so far very few studies have reported methods for establishing a complete closed mesh model of scratch data which is the precondition of online rail-repair as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [ 29 ] proposed a defect inspection method of rail surface based on the line-structured light. Santur et al [ 30 ] described a computer-vision based approach allowing for a fast-contactless detection of the rail surface and lateral defects such as fracture, scouring and wear with high accuracy. However, so far very few studies have reported methods for establishing a complete closed mesh model of scratch data which is the precondition of online rail-repair as mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…Görüntü iĢleme teknikleri; bilgisayar türevi makineler tarafından, görüntüden anlam çıkarmak için kullanıldıkları gibi görüntüdeki gürültüleri eleme, görüntünün renk dengesini düzenleme ve daha yüksek çözünürlüklü görüntüler elde etme gibi görüntü iyileĢtirme iĢlemleri için de yaygın olarak kullanılırlar. GeliĢen teknoloji ile birlikte günümüzde görüntü iĢleme yöntemlerinin birçok alanda kullanımları mevcuttur [1,2].…”
Section: Gi̇ri̇ş (Introduction)unclassified
“…There are many faults on the rail line. As a result of these failures, the train and rail track components may be damaged [1][2][3]. Generally, the areas where failures occur are the rail mantle and the rail surface.…”
Section: Introductionmentioning
confidence: 99%
“…In the non-contact methods, the railway line is monitored using laser or normal cameras [8][9][10]. In recent years, image processing based methods _______________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________________, 1,2,3 have been developed and contactless status monitoring has been performed. Non-contact condition monitoring methods are quite fast compared to contact condition monitoring methods.…”
Section: Introductionmentioning
confidence: 99%